Intraseasonal Dynamics of River Discharge and Burned Forest Areas in Siberia - Evgenii I. Ponomarev; Tatiana V. Ponomareva; Anatoly S. Prokushkin (Water, 2019)
This study demonstrates the dependence between the forest burning rates and abnormal decrease in Siberian river discharges under the conditions of the permafrost zone. Our study area is in Central Siberia and Eastern Siberia/Yakutia. Four rivers (Podkamennaya Tunguska, Lower Tunguska, Aldan, and Viluy) were selected for the study. We analyzed the long-term and seasonal variation of river discharges (archive of The Global Runoff Data Centre for 1939−2015) together with the forest burning dynamics within the river basins (archive of Sukachev Institute of Forest for 1996−2015). We compared the discharges per year with the 77-year average value. Abnormally low levels of discharge constituted 58−78% of the averaged annual rate. An analysis of available chronologies of extreme fire events and relative burned areas (RBAs) showed a high correlation with intra-seasonal data on the runoff minima. The most significant response of river discharges to the wildfire effect was shown for the late summer/autumn season after extreme wildfires during the summer period. The deficit of the runoff was not explained by a low precipitation. Late summer and autumn anomalies of discharge were typical ( r = −0.57…−0.77, p < 0.05) for rivers of Central Siberia in seasons of extreme forest burning. The correlation was lower for rivers of Eastern Siberia/Yakutia.